Wide Area Motion Tracking Using Consumer Hardware - Schönauer, Christian; Kaufmann, Hannes (International Journal of Virtual Reality, 2013)
In this paper we present a wide area tracking system based on consumer hardware and available motion capture modules and middleware. We are using multiple depth cameras for human pose tracking in order to increase the captured space. Commercially available cameras can capture human movements in a non-intrusive way, while associated software-modules produce pose information of a simplified skeleton model. We calibrate the cameras relatively to each other to seamlessly combine their tracking data. Our design allows an arbitrary number of sensors to be integrated and used in parallel over a local area network. This enables us to capture human movements in a large arbitrarily shaped area. In addition we can improve motion capture data in regions, where the field of view of multiple cameras overlaps, by mutually completing partly occluded poses. In various examples we demonstrate, how human pose data is being merged in order to cover a wide area and how this data can easily be used for character animation in a virtual environment.